Using Interactive Application in Creating Documentary entitled “ a peek of…: Bandaraya Ipoh Edition - Abdullah, Mohammad Rajab Farukhan; Abd Ghani, Dahlan (Journal of Computing Technologies and Creative Content, 2021)
This research aims to develop an application strategy by using Interactive Documentaries on the travel industry direct to pass on the information in a more powerful manner, clear and beguiling. This research will in like manner focus on the speed of response by the zeroed in on respondents from local and abroad tourists. Subsequently, the various characteristics, deficiencies, rightness, and missteps of the current objectives could be much more adequately tended to in the course of action of the limited-time methods. As needs are, these findings will improve Malaysia's travel industry method as per the progress of development. The 3P (Pre-production, Production, and Post-production) Model will be utilized in this study to guarantee that the data is conveyed adequately. Along this line, this project will fill in to redesign the social travel industry in Ipoh, through cutting-edge and possible techniques.